Numerical study of L-mode waves with a magnetic field-aligned density duct in the polar ionosphere - Naeem, Danish; Lee, Dong Hun; Kim, Kihong (Physics of Plasmas, 2025)
In the polar regions of the ionosphere, large-scale magnetic field-aligned irregularities serve as waveguides. These irregularities compel ordinary (O)-mode waves to travel along geomagnetic field lines as left-handed polarized (L)-mode waves, enabling them to pass through the O-mode reflection height beyond the standard radio windows. Previous experiments at the European Incoherent Scatter Scientific Association heating facility have shown that L-mode waves can excite plasma modes or escape from the ionosphere. We have developed a numerical model that adopts an arbitrary magnetic field-aligned density duct to investigate the characteristics of L-mode waves in an inhomogeneous ionosphere. The results demonstrate that L-mode waves can efficiently transmit through the plasma resonance layer of the duct to propagate beyond the O-mode reflection height. Upon reflection from their respective reflection height, they can transform into Z-mode waves, enhancing the amplitude of the electric fields at the plasma resonance. Our findings clarify how L-mode waves facilitate wave propagation beyond the O-mode reflection height and affect magnetic zenith effects.
Keywords: Density duct; Geomagnetic field lines; L-modes; Large-scales; Lefthanded; Magnetic field aligned irregularities; Magnetic-field; Plasma resonance; Polar ionospheres; Polar Regions